SIGNIFICANCE, USE AND PRODUCTION OF POTATOES - Boltaev Murodbek Allayorovich (Galaxy International Interdisciplinary Research Journal, 2022)
The article provides brief information about the meaning, use and production of potatoes, the technology of mechanized harvesting and post-harvest processing of tubers, outlines the theoretical foundations and storage technology, highlights the technology of pre-sale commodity processing, briefly describes the methods of processing potatoes for potato products and for technical purposes.